ANALYSIS OF THE JOURNALISTIC LANGUAGE IN THE INFORMATION CAPTIONS ON THE @COPPAMAGZ ACCOUNT ON INSTAGRAM - HALIMATUSSA'DIYAH; WAHYUNENGSIH (English Literature Department, Faculty of Economics, Law, and Humanities, 2023)
Journalistic language is the language journalists use in writing, presenting, and disseminating actual, factual, and reliable news and information to attract viewers' attention. There are 17 main characteristics of journalistic language, namely simple, short, concise, straightforward, clear, pure, interesting, democratic, populist, logical, grammatical, avoiding speech informal, avoiding foreign words and terms, choosing the right words (diction), prioritizing active sentences, avoiding technical words terms, and complyingwith ethical rules. This study uses a qualitative approach. Methods of data collection in this study use observation and document analysis. This study aims to determine the application of journalistic language to the information caption used by the @coppamagz account on Instagram. The theory used in this study is the Sumadiria theory (2016). The research results on the application of journalistic language in information captionson the @coppamagz account on Instagram, which was published on 24 February – 24 March 2023, show that it almost meets the characteristics of using journalistic language. But also found some errors in the application of journalistic language. Following are the results of the frequency of data obtained: (1) 8 simple aspects, (2) 8 short aspects, (3) 10 concise aspects, (4) 10 straightforward aspects, (5) 10 clear aspects, (6) 10 pure aspects,(7) 10 interesting aspects, (8) 10 democratic aspects, (9) 7 populist aspects, (10) 10 logical aspects, (11) 8 grammatical aspects, (12) aspects avoiding speech (informal) totaling 8, (13) aspects avoiding foreign words and terms totaling 4, (14) aspects choosing the right words (diction) totaling 10, (15) aspects prioritizing active sentences totaling 8, (16) aspects avoiding technical words or terms as many as 7, and (17) aspects of complying with ethical rules as many as 10.